Influence of highway three‐dimensional coordination on drivers' perception of horizontal curvature and available sight distance. Issue 2 (1st June 2013) - Moreno, Ana Tsui; Garcia, Alfredo; Camacho‐Torregrosa, Francisco Javier; Llorca, Carlos
Abstract : Drivers' road perception is an important human factor of comfort and safety on driving. Available sight distance of crest vertical curves superimposed on horizontal curves can be geometrically optimised by applying 3D coordination criteria. However, drivers might not perceive available sight distance improvements. Two approaches were used to investigate the effect of geometrical optimised design on perceived sharpness and visibility of isolated crest vertical curves overlapped with horizontal curves. A survey‐based approach was used to evaluate subjective perception of 100 drivers. Three‐dimensional renderings were displayed to subjects; who were asked to rank the curves by sharpness and sight distance. Moreover, 50 of those drivers previously participated on a driving simulation experiment involving the same curves, so objective driving data were collected too. Drivers' survey results indicate that driver's curve perception depends on the algebraic difference of grades while coordination of vertical and horizontal curves does not appear to affect this perception. On the other hand, the operating speeds on different curves were not statistically different from each other. Surprisingly, the operating speeds on a flat curve tended to be lower than on the vertical crest curves superimposed on the same horizontal curve. Likely causes are discussed in the paper.